Upaya dalam Menghindari Penggunaan Narkotika bagi Generasi Z - Cholidah Utama; Ahmad Ari Fatullah (AKM, 2024)
There are many things that can be done by everyone in order to avoid illegal use of narcotics. However, this can be done by people who already understand narcotics, both positively and negatively. Therefore, for people who are not too familiar with narcotics, it is necessary to provide a special understanding by related parties. Even more so for generation Z, because this generation needs to be protected from the dangers of narcotics. Thus, the author needs to do community service to provide an understanding of narcotics, especially tips on avoiding illegal use of narcotics. This community service uses the seminar method in order to provide material to the community. The object of dedication is the students of SMK Negeri 3 Lubuk Linggau. While the location of the service is carried out in the meeting room/hall of SMK Negeri 3 Lubuk Linggau. This service has succeeded in increasing the knowledge of students at SMK Negeri 3 Lubuk Linggau about narcotics and understanding how to avoid them.